2014
DOI: 10.3109/02688697.2014.887656
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported nasal morbidity following endoscopic endonasal skull base surgery

Abstract: Endoscopic endonasal skull base surgery is associated with a low level of patient-reported post-operative nasal morbidity. There is no significant difference in frequency of crusting, blockage, pain or discharge between pituitary and other anterior skull base pathology groups. However, anterior skull base surgery would appear to be associated with an increased rate of anosmia post-operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 13 publications
3
48
0
Order By: Relevance
“…None of these variables achieved statistical significant risk factors for nasal crusting [6,9]. However, de Almeida and colleagues, found that the only risk factor for nasal discharge was surgical complexity [6].…”
Section: Intraoperative Risk Factors For Sinonasal Morbiditymentioning
confidence: 91%
See 4 more Smart Citations
“…None of these variables achieved statistical significant risk factors for nasal crusting [6,9]. However, de Almeida and colleagues, found that the only risk factor for nasal discharge was surgical complexity [6].…”
Section: Intraoperative Risk Factors For Sinonasal Morbiditymentioning
confidence: 91%
“…However, it should be noted that the two studies are from the same center and likely have overlapping patients. In contrast, Gallagher and colleagues observed different results of patient-reported nasal morbidity following EESBS [9]. One hundred and twenty four patients were interviewed with a median follow-up of 15 months.…”
Section: Time To Resolve Nasal Signs and Symptomsmentioning
confidence: 92%
See 3 more Smart Citations